Mitigating the risk of opioid abuse through a balanced undergraduate pain medicine curriculum - Morley-Forster PK; Pergolizzi JV; Taylor Jr R; Axford-Gatley RA; Sellers EM (Journal of Pain Research, 2013)
Patricia K Morley-Forster,1,2 Joseph V Pergolizzi,3–5 Robert Taylor Jr,5 Robert A Axford-Gatley,6 Edward M Sellers71Department of Anesthesia and Perioperative Medicine, University of Western Ontario, London, ON, Canada; 2Outpatient Pain Clinic, St Joseph’s Hospital, London, ON, Canada; 3Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 4Department of Pharmacology, Temple University School of Medicine, Philadelphia, PA, USA; 5NEMA Research Inc, Naples, FL, USA; 6Clinical Content and Editorial Services, Complete Healthcare Communications, Inc, Chadds Ford, PA, USA; 7DL Global Partners Inc, Toronto, ON, CanadaAbstract: Chronic pain is highly prevalent in the United States and Canada, occurring in an estimated 30% of the adult population. Despite its high prevalence, US and Canadian medical schools provide very little training in pain management, including training in the safe and effective use of potent analgesics, most notably opioids. In 2005, the International Association for the Study of Pain published recommendations for a core undergraduate pain management curriculum, and several universities have implemented pilot programs based on this curriculum. However, when outcomes have been formally assessed, these initiatives have resulted in only modest improvements in physician knowledge about chronic pain and its treatment. This article discusses strategies to improve undergraduate pain management curricula and proposes areas in which those efforts can be augmented. Emphasis is placed on opioids, which have great potency as analgesics but also substantial risks in terms of adverse events and the risk of abuse and addiction. The authors conclude that the most important element of an undergraduate pain curriculum is clinical experience under mentors who are capable of reinforcing didactic learning by modeling best practices.Keywords: chronic pain, curricular content, medical education, opioids, pain education, pain knowledge, physician training, teaching